Vaginal leiomyoma: medical imaging and diagnosis in a resource low tertiary hospital: case report - Thomas Obinchemti Egbe; Fidelia Mbi Kobenge; Junette Arlette Mbengono Metogo; Emmanuella Manka'a Wankie; Paul N. Tolefac; Eugene Belley-Priso (BMC, 2020)
Abstract Background In the literature under review there are about 300 reported cases of vaginal leiomyomas with none from Cameroon. We report a case of vaginal leiomyoma and highlight the diagnostic challenges faced at the Douala Referral Hospital (DRH), Cameroon. Case presentation A 36-year-old G3P3002 sexually active Cameroonian married woman reported dysuria, dyspareunia, cessation of sexual intercourse and offensive smelling vaginal discharge for 6 months and a 3-year history of a vaginal tumour; she was misdiagnosed despite ultrasonography and magnetic resonance imaging (MRI) but was corrected by an experienced radiologist. She underwent first look laparoscopy, surgical excision of the tumour through the vagina and histopathology analysis that confirmed leiomyoma. Conclusion Posterior location of vaginal leiomyomas found in this case is a rare occurrence. The diagnosis is based on careful examination and preoperative imaging (ultrasonography and MRI). However, the definitive diagnosis is usually made intra-operatively. We combined laparoscopic exploration of the internal genital organs and per vaginal excision of the vaginal leiomyoma. Thus, we recommend frozen section biopsy to exclude leiomyosarcoma.